Strategi Peningkatan Kinerja Pranata Laboratorium Pendidikan Fakultas Tarbiyah dan Ilmu Keguruan (FTIK) IAIN Kerinci - Yani, Ahmad Yani; Gusmanto, Rizki (Jurnal Ekonomi Manajemen dan Bisnis (JEMB), 2024)
(PLP) at the Faculty of Tarbiyah and Teacher Training (FTIK) IAIN Kerinci. This type of research uses field studies (field research). The data in this research is in the form of information, actions, activities that can be used as studies related to the research focus of Strategy for Increasing the Performance of Laboratory Institutions. The research results show that the most important alternative strategy and the main priority in order to improve the performance of PLP at the FTIK IAIN Kerinci Faculty is improving welfare. The research results also show that the actor most involved and influential in improving PLP performance is the head of the laboratory, while the main priority goal in improving PLP performance is increasing PLP professionalism. PLP performance can be improved by paying attention to their welfare in line with the implementation of PLP functional positions. Apart from that, the head of the laboratory should be able to encourage and motivate PLPs to improve their performance, so that PLPs are able to work independently and professionally and provide the best service oriented towards customer satisfaction. Key Words : strategy, Performance improvement, PLP